PENDIDIKAN ISLAM SEBAGAI SEBUAH SISTEM: ANALISIS PERAN DAN TANTANGAN DI ERA GLOBALISASI - Firmantara Rabbani, Faqih; Mohammad Iqbal, Kiki; Taupik Kurahman, Opik (As-Sulthan Journal of Education, 2025)
Islamic education as a system represents a comprehensive unity of objectives, components, and values grounded in the principle of tawhid. This study aims to analyze the concept of Islamic education as an integral system within the national education framework and to identify its role, challenges, and prospects in the globalization era. The research employed a descriptive qualitative approach through a literature review of classical and contemporary sources. The findings reveal that Islamic education has a holistic character that balances knowledge and faith, worldly and spiritual dimensions, as well as rationality and morality. As part of the national education system, Islamic education plays a strategic role in shaping national character and integrating spiritual values into learning. The integration of religious and general sciences is essential for Islamic education to remain relevant to modernity without losing its Islamic identity.